Apolipoprotein CIII links islet insulin resistance to β-cell failure in diabetes - Leibiger, Ingo B. (2015)
Insulin resistance and β-cell failure are the major defects in type 2 diabetes mellitus. However, the molecular mechanisms linking these two defects remain unknown. Elevated levels of apolipoprotein CIII (apoCIII) are associated not only with insulin resistance but also with cardiovascular disorders and inflammation. We now demonstrate that local apoCIII production is connected to pancreatic islet insulin resistance and β-cell failure. An increase in islet apoCIII causes promotion of a local inflammatory milieu, increased mitochondrial metabolism, deranged regulation of β-cell cytoplasmic free Ca2+ concentration ([Ca2+]i) and apoptosis. Decreasing apoCIII in vivo results in improved glucose tolerance, and pancreatic apoCIII knockout islets transplanted into diabetic mice, with high systemic levels of the apolipoprotein, demonstrate a normal [Ca2+]i response pattern and no hallmarks of inflammation. Hence, under conditions of islet insulin resistance, locally produced apoCIII is an important diabetogenic factor involved in impairment of β-cell function and may thus constitute a novel target for the treatment of type 2 diabetes mellitus.